PENGARUH OLAH TANAH KONSERVASI TERHADAP RETENSI AIR DAN KETAHANAN PENETRASI TANAH PADA LAHAN KERING MASAM DI LAMPUNG TIMUR - Netty Dwi Ariska; Neneng Laela Nurida; Zaenal Kusuma (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2016)
Intensive soil tillage without returning crop residues resulted in deterioration of physical properties, particularly soil water retention and soul penetration resistance, of dry land acid soils. One of efforts to overcome the impact of intensive soil tillage is implementation of conservation tillage. This study was aimed to determine the effects of the application of conservation tillage on soil penetration resistance and water retention on acid dry land of East Lampung. The treatments tested were conventional soil tillage (OT1), conventional soil tillage with application of 6 t maize residue ha-1 (OT2), soil tillage in row with application of 6 t maize residue ha-1 (OT3), and no soil tillage with application of 6 t maize residue ha-1(OT4). Parameters measured were soil organic matter content, soil bulk density, total pore space, water retention, soil penetration, and biomass of soybean. The results showed that OT4 treatment (no tillage with application of 6 t maize residue ha-1) had the lowest penetration resistance of 1.75 Mpa and highest water retention capabilities 10.42% compared with conventional tillage